2002
DOI: 10.1083/jcb.200109018
|View full text |Cite
|
Sign up to set email alerts
|

In vivo binding of active heat shock transcription factor 1 to human chromosome 9 heterochromatin during stress

Abstract: Activation of the mammalian heat shock transcription factor (HSF)1 by stress is a multistep process resulting in the transcription of heat shock genes. Coincident with these events is the rapid and reversible redistribution of HSF1 to discrete nuclear structures termed HSF1 granules, whose function is still unknown. Key features are that the number of granules correlates with cell ploidy, suggesting the existence of a chromosomal target. Here we show that in humans, HSF1 granules localize to the 9q11-q12 heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
122
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 36 publications
7
122
0
Order By: Relevance
“…Indeed, we have previously shown that HSP70 overexpression efficiently prevents the relocalization of HSF1 to the granules and the subsequent RNA polymerase II-dependent transcription of sat III repeats following heat exposure (Jolly et al, 2004). We also used a mutant of HSF1 that only contains the DNA-binding and trimerization domains (DBD+TRIM) and constitutively forms granules (Jolly et al, 2002). An interesting feature is that it acts as a dominant negative mutant, preventing the stressinduced relocalization of the endogenous HSF1 to the granules and the subsequent sat III transcription (Jolly et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we have previously shown that HSP70 overexpression efficiently prevents the relocalization of HSF1 to the granules and the subsequent RNA polymerase II-dependent transcription of sat III repeats following heat exposure (Jolly et al, 2004). We also used a mutant of HSF1 that only contains the DNA-binding and trimerization domains (DBD+TRIM) and constitutively forms granules (Jolly et al, 2002). An interesting feature is that it acts as a dominant negative mutant, preventing the stressinduced relocalization of the endogenous HSF1 to the granules and the subsequent sat III transcription (Jolly et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence was performed on formaldehyde-fixed cells as described previously (Jolly et al, 2002). DNA was counterstained with 250 ng/ml DAPI.…”
Section: Immunofluorescence and Microscopymentioning
confidence: 99%
“…Finally, in a number of cell types, Hsf1 accumulates in a few nuclear foci during stressful events (Sarge et al 1993). These granules, termed stress granules, were found to form on chromosome 9 heterochromatin of human cells (Jolly et al 2002). It was speculated that stress granules could represent sites of storage or buffering (or both) of active Hsf1.…”
Section: Other Aspects Of Hsf-hsf1 Regulationmentioning
confidence: 99%